You are on page 1of 4

𝑀(𝐵, 𝐶) = 𝑃−1

𝑀(𝐻, 𝐶) = 𝑄 −1

𝑀(𝐵, 𝐻) = 𝑃−1 · 𝑄 = 𝑅

b)

𝑣𝐵 = 𝑃−1 · 𝑣 = (−3, −4, −1, 3)

3
𝑣𝐻 = 𝑄 −1 · 𝑣 = (−3, −1, −1, )
2
det(𝐼 − 𝜆𝐼) = 0

𝜆1 = 1
𝜆2 = 1
{
𝜆3 = −2
𝜆4 = 3
𝑥 + 2𝑦 − 3 = 0
𝑟≡{
1−𝑧 =0
𝑥 + 3𝑦 + 14 = 0
𝑡≡{
5𝑦 + 𝑧 + 32 = 0
𝜋1 ∩ 𝜋2 = 𝑟 ∗
𝜋1 ≡ 𝜆(𝑥 + 2𝑦 − 3) + (1 − 𝑧) = 0
𝑃(0,0,0)

−3𝜆 + 1 = 0 → 𝜆 = 1⁄3 → 𝜋1 ≡ 1⁄3 (𝑥 + 2𝑦 − 3) + (1 − 𝑧) = 0

𝜋1 ≡ 𝑥 + 2𝑦 − 3𝑧 = 0

𝜋2 ≡ 𝜆(𝑥 + 3𝑦 + 14) + (5𝑦 + 𝑧 + 32) = 0


𝑃(0,0,0)

14𝜆 + 32 = 0 → 𝜆 = − 16⁄7

𝜋2 ≡ − 16⁄7 (𝑥 + 3𝑦 + 14) + (5𝑦 + 𝑧 + 32) = 0

𝜋2 ≡ 16𝑥 + 13𝑦 − 7𝑧 = 0

𝑥 + 2𝑦 − 3𝑧 = 0
𝑟∗ ≡ {
16𝑥 + 13𝑦 − 7𝑧 = 0
b)
⃗⃗⃗⃗⃗⃗⃗⃗ ⃗⃗⃗⃗⃗⃗⃗⃗⃗ 1 4 2 1
𝑃 0 𝑃1 = (1,4,2,1) , 𝑃0 𝑃2 = (2,0,2,4) ( ) ~ 𝑅𝑎𝑛𝑘 = 2
2 0 2 4

𝐿 ≡ (1, −1,0,1) + 𝛼(1,4,2,1) + 𝛽(2,0,2,4)


𝑥 = 1 + 𝛼 + 2𝛽
𝑦 = −1 + 4𝛼
𝐿≡{ ∀ 𝛼, 𝛽 𝜖 ℝ
𝑧 = 2𝛼 + 2𝛽
𝑡 = 1 + 𝛼 + 4𝛽
2𝑥 − 𝑦 + 2𝑧 − 2𝑡 − 1 = 0
𝐿≡{
8𝑥 − 𝑦 − 4𝑡 − 5 = 0
𝐿′ ≡ (−3,0,1, −1) + 𝛼(2, −1,2, −2) + 𝛽(8, −1,0, −4)

𝑥 = −3 + 2𝛼 + 8𝛽
𝑦 = −𝛼 − 𝛽
𝐿′ ≡ { ∀ 𝛼, 𝛽 𝜖 ℝ
𝑧 = 1 + 2𝛼
𝑡 = −1 − 2𝛼 − 4𝛽
2(−3 + 2𝛼 + 8𝛽) − (−𝛼 − 𝛽) + 2(1 + 2𝛼) − 2(−1 − 2𝛼 − 4𝛽) − 1 = 0
𝐿 ∩ 𝐿′ = {
8(−3 + 2𝛼 + 8𝛽) − (−𝛼 − 𝛽) − 4(−1 − 2𝛼 − 4𝛽) − 5 = 0
191 125
(𝛼, 𝛽) = (− , )
214 214
12 33 84 166
𝑃′ = (− , ,− ,− )
107 107 107 107